2007
DOI: 10.1007/s00264-007-0477-8
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical markers of bone turnover in aseptic loosening in hip arthroplasty

Abstract: The aim of this study was to determine the diagnostic value of systemic biochemical markers of bone turnover in aseptic loosening in hip arthroplasty, namely the urine levels of three bone resorption peptides -crosslinked n-telopeptides (NTX), c-telopeptides (CTX I) and deoxypyridinoline (DPD). We compared 52 patients with surgically proven component loosening with 52 patients without clinical or radiological signs of endoprosthetic loosening and 52 healthy individuals. All three markers were measured using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
4
7
0
Order By: Relevance
“…The elevated peri-implant bone resorption was consistent with the dramatic increases in serum concentrations of CTX-1 and cathepsin K. Previous studies of CTX-1 reported variable ability to discriminate between patients with stable and patients with loosened implants, [21][22][23] while cathepsin K has not been studied as a biomarker for osteolysis. Interestingly, we found no difference in the concentration of TRAP 5b, which contradicts some previous clinical reports.…”
Section: Biomarkers Of Bone Metabolism Have Received Considerable Attsupporting
confidence: 62%
“…The elevated peri-implant bone resorption was consistent with the dramatic increases in serum concentrations of CTX-1 and cathepsin K. Previous studies of CTX-1 reported variable ability to discriminate between patients with stable and patients with loosened implants, [21][22][23] while cathepsin K has not been studied as a biomarker for osteolysis. Interestingly, we found no difference in the concentration of TRAP 5b, which contradicts some previous clinical reports.…”
Section: Biomarkers Of Bone Metabolism Have Received Considerable Attsupporting
confidence: 62%
“…β-CTX is a commonly measured biomarker of osteoclastic bone resorption used to predict bone mass loss, response to treatment, and risk of osteoporotic fractures 40 . A previous study evaluating the utility of urinary β-CTX as a biomarker of peri-implant osteolysis reported no difference between groups 41 , which is consistent with results in the current study. α-CTX is emerging as a biomarker for osteolysis caused by the skeletal invasion of metastatic cancers, such as breast cancer 27; 28 .…”
Section: Discussionsupporting
confidence: 92%
“…As wear-induced peri-implant osteolysis is a long-term process of net bone resorption that precedes aseptic loosening in the clinic, we chose to sample at 12 weeks of SPC administration in order to observe osteoclasts. Elevated levels of serum CTX-1, a biomarker of bone resorption, have been reported in patients with loosened implants, as compared to those with stable implants (Wilkinson et al, 2003;Streich et al, 2009), which corroborates our results. Moreover, we found that elevated levels of serum CTX-1 were reduced by SPC.…”
Section: Figuresupporting
confidence: 92%